THE ROLE OF YOUNG PEOPLE IN REALIZING GENDER EQUALITY IN THE MIDST OF STRONG PATRIARCHAL CULTURE IN NTT AND PAPUA - Rudi Kogoya (International Relations Study Program of Universitas Kristen Indonesia (UKI), 2023)
This paper discusses the role of young people in realizing gender equality in the midst of a strong patriarchal culture in two regions of Indonesia, namely East Nusa Tenggara and Papua. The strong patriarchal culture in East Nusa Tenggara and Papua causes women to experience violence in the home to the household. From the data obtained, domestic violence (KDRT) that occurred in East Nusa Tenggara was caused by the existence of belis in NTT and the influence of dowry on Papuan women so that there was a sense of male authority over these women. The rate of violence has increased over the years and this requires a serious subscription both from the government and from the community. This paper uses qualitative methods with case studies, interviews and documentation studies through journals, books and research results. To minimize violence against women, it is necessary to have the role of young people in the family, education and society through the socialization of the importance of gender equality in the family and society. Keywords: Role of Youth, Gender Equality, Patriarchal Culture, NTT, Papua